Energy Consumption, Governance Quality and Sustainable Development Nexus: Empirical Evidence from MENA Countries - Lassoued, Mongi (International Journal of Energy Economics and Policy, 2021)
The objective of this paper is to empirically examine whether energy consumption and governance quality affect sustainable development in 17 Middle East and North Africa (MENA) countries over the period 1984-2018 using a simultaneous equation model (SEM). Empirical results provide evidence that control of corruption and the institutional or governance quality of are complementary and essential for energy consumption to have an indirect positive impact on sustainable development. The results also show that sustainable development reacts negatively to energy consumption because the poor governance quality in MENA countries. These empirical insights are of particular interest to policymakers to improve the governance quality and implement sound economic policies to support economic development. Keywords: governance quality, energy consumption, economic growth, simultaneous equation model JEL Classifications: H11, Q01, Q43, C30 DOI: https://doi.org/10.32479/ijeep.11259